Clinical scenario, contraceptive awareness and epidemiological trends in adolescent girls: an outpatient review at a tertiary care institute - Katke, Rajshree Dayanand; Pal, Sanchari; Nawarange, Shubhangi; Waseem, Shaikh Shaima; Deshpande, Tanmay; Pawar, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Adolescence is a vulnerable time in a child’s life, both in terms of physical and psychological changes. This study aims to identify some of the common gynecological problems faced by adolescent girls and throws light on some common psychological stressors prevalent among adolescent girls. An attempt has been made to estimate the presence of contraception awareness among adolescent girls as well. Methods: This is an outpatient-based, observational, prospective study carried out for a period of six months between December 2023 to May 2024 wherein a group of 50 adolescent girls between the ages of 10-19 years, who have visited the gynecology outpatient department at St. George Hospital, Mumbai with specific complaints have been enrolled. Results: The most common age group identified in the study was between 18-19 years of age. The most prominent gynecological complaint was menstrual irregularities found in 34% of the girls followed by abdominal pain in 30%. Puberty menorrhagia was found in 12% of the subjects. Anxiety was the most common psychological stressor seen in 64% of girls with temperament issues coming a close second in 40% of subjects. Contraception awareness was present in 64% of the girls and the barrier method was the most widely known. Conclusions: A lot of adolescents while developing the common gynecological problems expected during adolescence, also develop a significant number of mental stressors. With more focussed research identifying the problems specifically occurring during adolescence, we can hope to provide a holistic approach while dealing with adolescent health.